Solution: Given:1. A → 2B, ΔH1 2. B → C + D, ΔH2 3. E → 2D, ΔH3ΔH of A → 2C + E is:A. ΔH1 + 2ΔH2 – ΔH3 B. ΔH2 - ΔH2 – ΔH3 C. ΔH3 – ΔH3 D. ΔH1 + 2ΔH1 – ΔH2 E. None of the above

Problem

Given:

1. A → 2B, ΔH

2. B → C + D, ΔH2 

3. E → 2D, ΔH3

ΔH of A → 2C + E is:

A. ΔH1 + 2ΔH2 – ΔH3 

B. ΔH2 - ΔH2 – ΔH3 

C. ΔH3 – ΔH3 

D. ΔH1 + 2ΔH1 – ΔH2 

E. None of the above

Solution

We’re being asked to determine the expression for the enthalpy change (ΔHrxn) for the chemical reaction:


 A → 2C + E


We can use Hess’s Law to determine the enthalpy change of the overall reaction from the given reactions:


1. A → 2B                                         ΔH1 

2. B → C + D                                    ΔH2 

3. E → 2D                                         ΔH3


We now need to find a combination of reactions that when added up, gives us the overall reaction.


Solution BlurView Complete Written Solution